2014
DOI: 10.1242/jcs.145334
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-independent stabilization of MHC class I molecules breaches cellular quality control*

Abstract: The intracellular trafficking of major histocompatibility complex class I (MHC-I) proteins is directed by three quality control mechanisms that test for their structural integrity, which is correlated to the binding of high-affinity antigenic peptide ligands. To investigate which molecular features of MHC-I these quality control mechanisms detect, we have followed the hypothesis that suboptimally loaded MHC-I molecules are characterized by their conformational mobility in the F-pocket region of the peptide-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 95 publications
(83 reference statements)
11
90
1
Order By: Relevance
“…Evaluation of association and dissociation parameters of a battery of peptides, containing targeted departures from the model, revealed that peptide acquisition by H-2K b takes place in two distinct phases. During the first phase, the peptide-binding groove of H-2K b accepts a wide range of candidates, including even amino acid side chains much larger than their optimal size, which implies significant flexibility in the anchor residue-accepting pockets (17,(19)(20)(21)(22). Following the initial association event, ill-suited peptides exhibit greater propensity for dissociation and are thus selected against.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of association and dissociation parameters of a battery of peptides, containing targeted departures from the model, revealed that peptide acquisition by H-2K b takes place in two distinct phases. During the first phase, the peptide-binding groove of H-2K b accepts a wide range of candidates, including even amino acid side chains much larger than their optimal size, which implies significant flexibility in the anchor residue-accepting pockets (17,(19)(20)(21)(22). Following the initial association event, ill-suited peptides exhibit greater propensity for dissociation and are thus selected against.…”
Section: Discussionmentioning
confidence: 99%
“…Structural Flexibility in the Peptide-Binding Groove of H-2K b . The peptide-binding groove should be flexible to accommodate expanded anchors (17)(18)(19)(20)(21)(22) (Table S4). In all structures the peptides could be resolved and fit into the electron density (Fig.…”
Section: Association and Disassociation Kinetics Of 9-mer Peptide Varmentioning
confidence: 99%
“…The unfolded protein fraction was calculated from the mean residue ellipticity (u) according to the following standard method: fraction unfolded (%) = (u 2 uN)/(uU 2 uN), where uN and uU are the mean residue ellipticity values in the fully folded and fully unfolded states, respectively. The melting temperature (Tm) was determined by fitting the data to the denaturation curves with the Origin 8.0 program (Origin Lab) as previously described (28)(29)(30).…”
Section: Thermostability Of P/uaa-b2mmentioning
confidence: 99%
“…Retroviral expression, microscopy and flow cytometry Retroviral expression, microscopy and flow cytometry were performed as in Hein et al, 2014.…”
Section: Cellsmentioning
confidence: 99%